The meaning of the Arabic sentence in the light of the contextual theory theories of mental space (Journal of the College of Basic Education, 2023)
Throughout its long history, linguistic studies have presented multiple theories and various approaches.One of them is his interests, foundations and different concepts from which he bases his conception of language. With the difference in these theories and approaches and the difference in their focus on the different aspects of the language, I tried These theories, in their entirety, require that the study of language be evaluated on solid, objective, scientific foundations. taste or personal impressions, because the aim of these approaches and theories is to promote the study of